CD4+CD25+ T regulatory cells in renal transplantation - Cheung, Jason; Zahorowska, Beata; Suranyi, Michael; Wong, Jeffrey K. W.; Diep, Jason; Spicer, Stephen T.; Verma, Nirupama D.; Hodgkinson, Suzanne J.; Hall, Bruce M. (Frontiers in Immunology, 2022)
The immune response to an allograft activates lymphocytes with the capacity to cause rejection. Activation of CD4+CD25+Foxp3+T regulatory cells (Treg) can down-regulate allograft rejection and can induce immune tolerance to the allograft. Treg represent <10% of peripheral CD4+T cells and do not markedly increase in tolerant hosts. CD4+CD25+Foxp3+T cells include both resting and activated Treg that can be distinguished by several markers, many of which are also expressed by effector T cells. More detailed characterization of Treg to identify increased activated antigen-specific Treg may allow reduction of non-specific immunosuppression. Natural thymus derived resting Treg (tTreg) are CD4+CD25+Foxp3+T cells and only partially inhibit alloantigen presenting cell activation of effector cells. Cytokines produced by activated effector cells activate these tTreg to more potent alloantigen-activated Treg that may promote a state of operational tolerance. Activated Treg can be distinguished by several molecules they are induced to express, or whose expression they have suppressed. These include CD45RA/RO, cytokine receptors, chemokine receptors that alter pathways of migration and transcription factors, cytokines and suppression mediating molecules. As the total Treg population does not increase in operational tolerance, it is the activated Treg which may be the most informative to monitor. Here we review the methods used to monitor peripheral Treg, the effect of immunosuppressive regimens on Treg, and correlations with clinical outcomes such as graft survival and rejection. Experimental therapies involving ex vivo Treg expansion and administration in renal transplantation are not reviewed.